2021
DOI: 10.1097/nmd.0000000000001323
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Linking Different Types of Childhood Trauma to Somatic Symptoms in a Subclinical Sample of Female College Students

Abstract: Research has shown that women are more prone to childhood trauma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…Experiential avoidance may initially be a protective factor, in that people are able to temporarily move away from distress by using avoidance as a coping mechanism; however, their symptoms may worsen over time (Bakker et al, 2019). We found that CDAV was positively associated with experiential avoidance in the present study, which supports both GST and previous research (Agnew, 1992; Bhuptani et al, 2019; Daneshvar et al, 2022; Heshmati et al, 2021). These previous studies demonstrated that exposure to interpersonal victimization is likely to increase experiential avoidance among female victims.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Experiential avoidance may initially be a protective factor, in that people are able to temporarily move away from distress by using avoidance as a coping mechanism; however, their symptoms may worsen over time (Bakker et al, 2019). We found that CDAV was positively associated with experiential avoidance in the present study, which supports both GST and previous research (Agnew, 1992; Bhuptani et al, 2019; Daneshvar et al, 2022; Heshmati et al, 2021). These previous studies demonstrated that exposure to interpersonal victimization is likely to increase experiential avoidance among female victims.…”
Section: Discussionsupporting
confidence: 93%
“…For female adolescents, experiencing CDAV is likely to induce strain and drive them to avoid further exposure to corresponding negative experiences. Additionally, empirical evidence indicates that experiential avoidance is a nonadaptive coping method for various adverse life experiences, such as the COVID-19 pandemic (Seçer & Ulaş, 2021), rape (Bhuptani et al, 2019), childhood maltreatment (Heshmati et al, 2021), and disordered eating (Skinner et al, 2017).…”
Section: Direct Association Between Cdav and Experiential Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…The PHQ-15 is often used as a measure of somatic symptom proneness (eg, Ref. [ 43 ]), and it has been shown to be useful in identifying somatic symptom disorder [ 44 ]. Each item assesses the degree to which individuals experience a specific somatic symptom rated on a scale from 0 (not bothered at all) to 2 (bothered a lot), with higher scores indicating a greater severity of somatic symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…For example, children or adolescents in their early stages of psychological development are particularly susceptible to the impact of negative life events and are at a higher risk of developing somatic symptoms [ 11 ]. Additionally, previous research showed that the college students who have experienced high levels of childhood trauma reported more somatic symptoms, likely due to the stress associated with the transition period from adolescence to adulthood [ 12 ]. In particular, the college students face a range of academic and social demands and need to adapt to various psychological changes in preparation for their working lives, which can make this period one of the most stressful periods of an individual’s life.…”
Section: Introductionmentioning
confidence: 99%